Proposal of a Nonlinear Interaction of Person and Situation (NIPS) model - Schmitt, Manfred; Gollwitzer, Mario; Baumert, Anna; Blum, Gabriela S.; Gschwendner, Tobias; Hofmann, Wilhelm; Rothmund, Tobias (Frontiers in Psychology, 2013)
Marshall and Brown (2006) proposed a Traits as Situational Sensitivities (TASS) Model, which implies a systematic person  situation interaction. We review this model and show that it suffers from several limitations. We extend and modify the model in order to obtain a symmetric pattern of levels and effects for both person and situation factors. Our suggestions result in a general Nonlinear Interaction of Person and Situation (NIPS) Model. The NIPS model bears striking similarities to the Rasch model. Based on the symmetric nature of the NIPS model, we generalize the concept of weak and strong situations to individuals and propose the concepts of weak and strong persons. Finally, we discuss psychological mechanisms that might explain the NIPS pattern and offer ideas for future research.